Reconstruction of a Ross lost Cambrian Series 2 mixed siliciclastic-carbonate platform from carbonate clasts of the Shackleton Range, Antarctica - Rodriguez-Martinez, Marta; Buggisch, Werner; Menendez, Silvia; Moreno-Eiris, Elena; Perejon, Antonio (Earth and Environmental Science Transactions of the Royal Society of Edinburgh, 2022)
The presence of archaeocyath-bearing clasts from Cenozoic tills and Cambrian Mount Wegener Formation reveal erosion of a hidden Cambrian carbonate platform in Shackleton Range, Antarctica. We provide microfacies, paleontological, diagenetic and tectonically induced fabric data from carbonate clasts which, in addition to available geochemical and geochronological data from Shackleton Range, allow the paleoenvironmental reconstruction of a lost Cambrian Series 2 mixed siliciclastic-carbonate platform that was developed and eroded during the Ross orogeny. Carbonate production was dominated by non-skeletal grains in possibly restricted platform-interior and oolitic shoal complex settings, while open subtidal sub-environments (calcimicrobe carpets, calcimicrobe-archaeocyath patch reefs, muddy bottoms) were dominated by a diverse calcimicrobe assemblage and/or by secondary to accessory heterozoan assemblage (archaeocyaths and other sponges, chancelloriids, hyoliths, coralomorphs, trilobites, echinoderms). We describe a Botoman assemblage with 34 archaeocyathan species among 12 existing archaeocyathan genera. A new archaeocyath family Shackletoncyathidae is proposed. New species (Rotundocyathus glacius sp. nov., Buggischicyathus microporus gen. et sp. nov., Paragnaltacyathus hoeflei, Shackletoncyathus buggischi gen. et. sp. nov., Santelmocyathus santelmoi gen. et sp. nov., Wegenercyathus sexangulae gen. et sp. nov.) and Tabulaconus kordae coralomorph are reported from Antarctica for the first time. Archaeocyathan fauna share few species with contemporary fauna of South Australia (9) and even fewer with the Antarctic platforms of the Shackleton Limestone (2) or the Schneider Hills limestone (1). Similarity is greater with Antarctic allochthonous assemblages of Permo-Carboniferous tillites from Ellsworth Mountains (2), Cenozoic deposits from King George Island (4) or Weddell Sea (1). The Shackleton Range lost/hidden platform shows a distinct entity related with its tectonosedimentary evolution, in a possible back-arc basin on the Mozambique seaway during the E and W Gondwana amalgamation, which distinguishes it from those developed on the palaeo-Pacific margin of the E Antarctic craton.
CRIS-Team WoS Importer:2022-08-12